Water pollution management - Jivendra (New Delhi : A.P.H. Pub. Corp., 1995)
Study with reference to Orissa, India.
Includes statistical tables.
Keywords: Paper industry--Water supply; Paper industry--Waste disposal--Environmental aspects; Feed-water purification